Mesozoic Paleo-Pacific Subduction Beneath SW Borneo: U-Pb Geochronology of the Schwaner Granitoids and the Pinoh Metamorphic Group - Breitfeld, H. Tim; Davies, Lorin; Hall, Robert; Armstrong, Richard; Forster, Marnie; Lister, Gordon; Thirlwall, Matthew; Grassineau, Nathalie; Hennig-Breitfeld, Juliane; van Hattum, Marco W. A. (Frontiers in Earth Science, 2020)
The Schwaner Mountains in southwestern Borneo form a large igneous province with a complex magmatic history and poorly known tectonic history. Previously it was known that Cretaceous granitoids intruded metamorphic rocks of the Pinoh Metamorphic Group assumed to be of Paleozoic age. Jurassic granitoids had been reported from the southern Schwaner Mountains. Most ages were based on K-Ar dating. We present new geochemistry, zircon U-Pb and 40Ar/39Ar age data from igneous and metamorphic rocks from the Schwaner Mountains to investigate their tectono-magmatic histories. We subdivide the Schwaner Mountains into three different zones which record rifting, subduction-related and post-collisional magmatism. The Northwest Schwaner Zone (NWSZ) is part of the West Borneo Block which in the Triassic was within the Sundaland margin. It records Triassic to Jurassic magmatism during early Paleo-Pacific subduction. In contrast, the North Schwaner Zone (NSZ) and South Schwaner Zone (SSZ) are part of the SW Borneo (Banda) Block that separated from NW Australia in the Jurassic. Jurassic granitoids in the SSZ are within-plate (A-type) granites interpreted to have formed during rifting. The SW Borneo (Banda) Block collided with eastern Sundaland at c. 135 Ma. Following this, large I-type granitoid plutons and arc volcanics formed in the NWSZ and NSZ between c. 90 and 132 Ma, associated with Cretaceous Paleo-Pacific subduction. The largest intrusion is the c. 110 to 120 Ma Sepauk Tonalite. After collision of the East Java-West Sulawesi (Argo) Block, subduction ceased and post-collisional magmatism produced the c. 78 to 85 Ma Sukadana Granite and the A-type 72 Ma Sangiyang Granite in the SSZ. Rocks of the Pinoh Metamorphic Group mainly exposed in the NSZ, previously assumed to represent Paleozoic basement, contain abundant Early Cretaceous (110 to 135 Ma) zircons. They are interpreted as volcaniclastic sediments that formed contemporaneously with subduction-related volcanic rocks of the NSZ subsequently metamorphosed during intrusion of Cretaceous granitoids. There are no igneous rocks older than Cretaceous in the NSZ and older than Jurassic in the SSZ and there is no evidence for a continuation of a Triassic volcanic arc crossing Borneo from Sundaland to the east.